Pentingnya Perilaku Hidup Bersih dan Sehat dalam Rumah Tangga - Mulyadi, jesica -; Yusuf, Zuhriana K.; Nagaring, Sulaiman Putra (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
Clean and Healthy Living Behaviour (PHBS) is a promotional strategy to improve public health through behavioural change at the household level. Initial observations in Hutadaa Village indicate low implementation of PHBS, characterised by smoking indoors, inadequate sanitation, and suboptimal waste management. This activity aims to increase community understanding and awareness of PHBS implementation through educational interventions. The community service was carried out on 7 September 2025 as part of the UNG Thematic Community Service Programme using an educational approach through presentations, educational videos, and interactive discussions. The results of the activity showed an increase in participants' knowledge and motivation to implement PHBS indicators, such as proper hand washing practices, use of healthy toilets, consumption of nutritious food, and control of risky behaviours. Thus, community-based education has proven to be effective as an initial approach to health behaviour change. However, the sustainability of PHBS implementation requires environmental support, assistance, and cross-sector collaboration.